STUDI META ANALISA: STRATEGI REHEARSAL DAN MEMORI JANGKA PENDEK - Suparmi Suparmi (Jurnal Psikologi Tabularasa, 2010)
Abstract This article is a study meta analysis of the experimental literature that has examined the effect of rehearsal strategy to improve short-term memory. It reviewed 59 studies from 13 journals. The population are 1341 people with down syndrome and children with specifict language impairmen, who included in special school and mainstream school, and 3487 students and graduated students. The meta analysis shows that strategy rehearsal have moderate impact on short-term memory on individu with down syndrome and children with specifict language impairment, but rehearsal strategy didnt have strong correlation with short-term memory on student and graduated student. Keywords: Rehearsal Strategy , Short-term Memory